Study on surface properties of sodiumdodecyl sulfate and dodecyltrimethylammonium bromide mixed surfactants and their interaction with dyes. Issue 4 (April 2019) - Sachin, K.M.; Karpe, Sameer A.; Singh, Man; Bhattarai, Ajaya
Abstract: The antagonistic as well as synergetic interaction for dodecyltrimethylammonium bromide (DTAB) and sodiumdodecyl sulfate (SDS) mixed surfactants by using surface tension are investigated on the basis of the results obtained earlier, the efficiency of adsorption (p C 20 ), aggregation number ( N ), Γ Γ max, effective Gibbs free energy ( Δ G eff o ) and C M C C 20 are calculated additionally with three different temperatures at T = 293.15, 298.15 and 303.15 K as the detailed surface properties. The binding constants and standard free energy change of SDS and DTAB mixture with the interaction of (2.5× 10 −5 mol L –1 of methyl orange, MO and methylene blue, MB) are carried out by using UV-Vis spectroscopy at room temperature by using different models. The closer values of the binding constants and standard free energy change for SDS and DTAB mixture with the interaction of MO and MB are included in our investigations.